PROGRAM ASURANSI USAHA TANI PADI OLEH PT. ASURANSI JASA INDONESIA (PERSERO) DI KABUPATEN SOLOK - Yulia Bob Damayanti; Afriva Khaidir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
The occurrence or failure of harvest that is felt by farmers in the planting season greatly determines the survival of farmers’ daily lives. The purpose of this study is to see how the implementation of farm insurance by PT. Asuransi Jasa Indonesia (Persero) in solok Regency. The results of this study indicate that, first, there was a decline in the interest of farmers to participate in farm insurance in the next planting season, both human resources were insufficent in supporting farm insurance activities. Key words :Implementation, Rice Farming Insurance, Farm risk